On Progress and Faith in Progress: A Self-critical Author‘s Postscript - Loewenstein, Bedřich (Dějiny – teorie – kritika, 2010)
Articles appear on pp. 253-355 of the Dějiny – teorie – kritika 6/2009 journal, in which the authors comment critically on Faith in Progress – History of a European Idea. A paper by Bedřich Loewenstein, the author of this book, responds to the points raised in this debate on his text, as well as dealing with critical observations on the German edition of his work.